Effect of Slow Deep Breathing to Blood Pressure and Heart Rate Hypertensive Patients at Adventist Hospital in Bandar Lampung, Indonesia - Anderson, Elisa (11th International Scholars Conference, 2017)
Hypertension is the deadly degenerative diseases and its prevalence increases every year. Slow deep breathing (SDB) is a complementary therapy that can be used to control hypertension. The aim of this study is to analyze the effect of SDB therapy on blood pressure (BP) and heart rate (HR) of the hypertensive patients. A quasi experimental with pre and post-test of nonequivalent control group design. The sample of this study was 45 respondents and was selected through convenient sampling technique. Respondents were divided into control group (22) without therapy and experimental group (23) with SDB therapy twice daily for four days. The average of pre-BP (154/93.33 mmHg), post-BP (139.42/86.4 mmHg), pre-HR (88.76 times/minute), and post-HR (76.29 times/minute). There were significant differences in the effect of SDB therapy on TD and HR in the experimental group (pre-post intervention) (p<0.05). There were significant differences in the effect of SDB therapy on TD and HR in the control and experimental groups (p<0.05). There is a significant effect of SDB therapy on BP and HR controls. Further research needs to be done for the development of SDB therapy into an effective procedure in independent-nursing intervention to hypertensive patients.